NMR unveils an N-terminal interaction interface on acetylated-α-synuclein monomers for recruitment to fibrils - Yang, Xue (Proc Natl Acad Sci U S A, 2021)
Amyloid fibril formation of α-synuclein (αS) is associated with multiple neurodegenerative diseases, including Parkinson’s disease (PD). Growing evidence suggests that progression of PD is linked to cell-to-cell propagation of αS fibrils, which leads to seeding of endogenous intrinsically disordered monomer via templated elongation and secondary nucleation. A molecular understanding of the seeding mechanism and driving interactions is crucial to inhibit progression of amyloid formation. Here, using relaxation-based solution NMR experiments designed to probe large complexes, we probe weak interactions of intrinsically disordered acetylated-αS (Ac-αS) monomers with seeding-competent Ac-αS fibrils and seeding-incompetent off-pathway oligomers to identify Ac-αS monomer residues at the binding interface. Under conditions that favor fibril elongation, we determine that the first 11 N-terminal residues on the monomer form a common binding site for both fibrils and off-pathway oligomers. Additionally, the presence of off-pathway oligomers within a fibril seeding environment suppresses seeded amyloid formation, as observed through thioflavin-T fluorescence experiments. This highlights that off-pathway αS oligomers can act as an auto-inhibitor against αS fibril elongation. Based on these data taken together with previous results, we propose a model in which Ac-αS monomer recruitment to the fibril is driven by interactions between the intrinsically disordered monomer N terminus and the intrinsically disordered flanking regions (IDR) on the fibril surface. We suggest that this monomer recruitment may play a role in the elongation of amyloid fibrils and highlight the potential of the IDRs of the fibril as important therapeutic targets against seeded amyloid formation.